Kepatuhan Perawat Dalam Penggunaan Alat Pelindung Diri (APD) Untuk Memutus Rantai Penularan Covid – 19 Di RSUD Cut Meutia Aceh Utara - Fitriana Dewi; Mawar Hayati; Yusrawati Yusrawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Corona virus disease 2019 (covid-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a new type of virus that has not been previously identified in humans. Signs and symptoms include acute respiratory distress such as fever, cough and shortness of breath. The incubation period for this virus is on average 5-6 days with the longest incubation period being 14 days. Personal protective equipment (PPE) is a tool used by health workers to protect patients from various microorganisms in health workers. In addition, the PPE equipment used by health workers also aims to protect themselves while carrying out their duties. This study aims to analyze the compliance of nurses in the use of PPE to break the chain of transmission of Covid-19 at the Cut Meutia Hospital, North Aceh. The population of this study were all nurses who served in the inpatient room at the Cut Meutia Hospital, North Aceh, amounting to 130 nurses. The results of the study showed that knowledge about the use of Personal Protective Equipment (PPE) to break the chain of transmission of Covid-19 infection was good for 89 (68.5%) implementing nurses. Meanwhile, the compliance variable regarding the use of Personal Protective Equipment (PPE) to break the chain of transmission of Covid-19 infection was 88 (67.7%) implementing nurses. The hospital has an obligation to improve the safety and comfort of health workers, especially nurses in providing health services.